2022
DOI: 10.3390/coatings12040450
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Analysis on Flow Field of Paint Mist Recovery with Single Nozzle for Ship Outer Panel Spraying Robot

Abstract: In this paper, we design a kind of negative pressure vacuum recovery hood, arranged at the front of the spray gun nozzle by CFD simulation; this addresses the paint mist pollution problem of the robot spraying on the outer plate of the ship, and the nozzle is arranged at the center of the recovery hood. Three vacuum recovery hood schemes are designed as follows: Scheme A, a hemispherical recovery hood with a diameter of 1.2 m; Scheme B, with a diameter of 1.6 m; Scheme C, with a diameter of 2.0 m. The recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In addition, the simulation results based on the Euler-Lagrange approach show a larger dispersion angle in the short-axis direction compared to the spraying experiments. On the contrary, Li [89] and Yi et al [90,91], who are also from the same research group, considered it more suitable for modeling by the Euler-Lagrange approach, owing to the low volume fraction of the droplet phase. Moreover, this method can better conform to the particle-loaded flow model and better simulate the impingement behavior of paint droplets on the wall, which cannot be achieved by the Euler-Euler approach.…”
Section: Discussion On Numerical Models For Airless Spraying Simulati...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the simulation results based on the Euler-Lagrange approach show a larger dispersion angle in the short-axis direction compared to the spraying experiments. On the contrary, Li [89] and Yi et al [90,91], who are also from the same research group, considered it more suitable for modeling by the Euler-Lagrange approach, owing to the low volume fraction of the droplet phase. Moreover, this method can better conform to the particle-loaded flow model and better simulate the impingement behavior of paint droplets on the wall, which cannot be achieved by the Euler-Euler approach.…”
Section: Discussion On Numerical Models For Airless Spraying Simulati...mentioning
confidence: 99%
“…They also presented numerical studies on spray painting processes using different atomizers (including airless sprayers), which found that the impacting droplet characteristics of the atomizers show significant influences on the properties of the forming paint films [88]. Similarly, based on the Eulerian-Lagrange approach, Li [89] and Yi et al [90,91] modeled the airless spraying on large ship exterior panels, and investigated the effects of the spraying parameters and their liquid film thickness distribution. Selected simulation results are shown in Figure 6.…”
Section: Research On Film Formation Characteristics and Mechanismsmentioning
confidence: 99%
“…Eddy currents are prone to occur in the cavity, resulting in the accumulation of VOCs inside the recovery hood. The flow field of a spray gun integrated with a single-layer recovery hood was first discussed by Yi et al [34], and the flow field caused by vacuum recovery suction was also studied. The characteristics of the recovery hood were optimized to improve the efficiency of paint misting to 83.4%, meeting the engineering needs of paintmist recovery during spraying operations.…”
Section: Introductionmentioning
confidence: 99%
“…The flow field generated by vacuum recovery suction can not only recycle the overspray paint mist but also have a significant impact on the paint mist that should be deposited on the ship hull. In addition, the physical phenomenon of VOCs evaporation was not considered by Yi et al [34]. Although the aforementioned research studies have made a lot of conceptual improvements in the ship painting system with the recovery function, some functions of the prototype production are still unsatisfactory and need to be further improved.…”
Section: Introductionmentioning
confidence: 99%